THE ANALYSIS OF THE PARTURITION PROCESS BY THE METHOD OF COVARIANCE ANALYSIS - MIYAKE, Akihiko (Kodo Keiryogaku (The Japanese Journal of Behaviormetrics), 1977)
The anticipation of the time of parturition was tried by the multiple regression based on items which indicated the advance in pregnancy toward parturition. Four multiple linear regression function of log T were prepared for anticipation in primiparous women before and after the rupture and in multiparous women before and after the rupture, respectively, where T express the interval between the time when each item was measured and the time of parturition.Parturition Process was very different for each individual. But by the similar method as the Covariance Analysis, it was ascertained that the difference was suffciently expressed by constant which vary with each individual and linear coeffcient were common to each individual.